Comparison of physical education curriculum for the second cycle of basic education in Syria, Egypt and Jordan - وطفي, ألفت; معوض, وائل; برهوم, محمد (Latakia University Journal -Medical Sciences Series, 2021)
The aim of this research is to compare physical education curricula in the basic education stage second cycle (secondary school) between Syria, Egypt, and Jordan in order to conclude recommendations that would serve in developing the Syrian current curriculum. For this purpose, six variables of Kline's curriculum components including objectives, content, assessment methods, auxiliary tools, place, and time were studied. The researcher used Beriday's method for comparison. The results showed that the Syrian curriculum is old and there is a total absence of several basic elements of the curriculum, in addition to ambiguity and weakness in explaining the aforementioned elements, while the Jordanian curriculum was the most comprehensive and the clearest. In light of the research conclusions, we made some recommendations about the importance of designing and framing the elements of the Syrian curriculum in all-inclusive, accurate, and can’t be misunderstood. And those recommendations have been clarified with pointing out the strength and weaknesses points that distinguish every one of the curriculums that we had studied in detail. Which would help the Syrian curriculum planners to develop the current curriculum or design a new more effective one.